مبدأ حظر استخدام القوة في العلاقات الدولية حرب أوكرانيا دراسة حالة - فؤاد عبيدي; عبد الوهاب بشيش (My University, 2025)
Summary: The principle of the prohibition of the use of force in international relations is considered one of the fundamental principles enshrined in the United Nations Charter. While these principles are among the most important foundations upon which the United Nations is based to achieve its desired goals, the protection of human rights is also considered one of the essential basics of the organization. This has led to an exception to the prohibition of force for the protection of human rights. In the Russian-Ukrainian war, the principle of the prohibition of the use of force in international relations was not upheld, as this war demonstrated that the standard of interests among major powers is decisive in stopping wars or ensuring their continuation. It also revealed a double standard in dealing with conflicts, as Russia faced sanctions immediately after its attack on Ukraine, while the zionist entity has faced no sanctions despite more than a year and a half passing since its aggression on Palestine. ........................ المخلص يُعتبر مبدأ حظر استخدام القوة في العلاقات الدولية من المبادئ الأساسية المكرسة في ميثاق الأمم المتحدة، وإن كانت هذه المبادئ من أهم ما تقوم عليه منظمة الأمم المتحدة من أجل تحقيق أهدافها المنشودة، فإن حماية حقوق الإنسان هي الأخرى تعد من بين الأساسيات الضرورية للمنظمة هذا ما ولد استثناء عن حظر القوة لحماية حقوق الإنسان. في الحرب الروسية الأوكرانية، لم يتم تجسيد مبدأ حظر استخدام القوة في العلاقات الدولية، حيث بينت هذه الحرب أن معيار المصالح بين الدول الكبرى هو الفيصل في إيقاف الحروب أو العمل على استمراريتها، كما بينت الازدواجية في التعامل، إذ أن روسيا فُرِضت عليها عقوبات بعد هجومها مباشرة على أوكرانيا، بينما الكيان الصهيوني لم تُفرض عليه أي عقوبة رغم مرور أكثر من عام و نصف على عدوانها على فلسطين. .......................... resumé Le principe d'interdiction du recours à la force dans les relations internationales est l'un des principes fondamentaux inscrits dans la Charte des Nations Unies. Si ces principes comptent parmi les plus importants sur lesquels les Nations Unies se fondent pour atteindre leurs objectifs, la protection des droits de l'homme est également l'un des fondements essentiels de l'organisation. C'est ce qui a créé une exception à l'interdiction du recours à la force pour protéger les droits de l'homme. Dans la guerre russo-ukrainienne, le principe d'interdiction du recours à la force dans les relations internationales n'a pas été incarné. Cette guerre a démontré que le critère des intérêts entre grandes puissances est le facteur déterminant pour arrêter ou poursuivre les guerres. Elle a également démontré la duplicité des relations, la Russie ayant été soumise à des sanctions immédiatement après son attaque contre l'Ukraine, tandis que l'entité sioniste n'a subi aucune sanction, malgré plus d'un an et demi d'agression contre la Palestine.
Keywords: Keywords Principle; power; ban; conflict; crisis; international relations; mechanisms; justifications; الكلمات المفتاحية مبدأ، قوة، حظر،نزاع، الأزمة، العلاقات الدولية، آليات، مبررات.; Mots-clés Principe; pouvoir; interdiction; crise; relations internationales; mécanismes; justificatifs